One Pot & Slow Cooking : Essential recipes - Edited by Steer, Gina (London Flame Tree Publishing, 2008)
A companion for anyone who: wants a scrumptious, slow-cook-style meal, lacks facilities or wishes to minimize washing up. With a wide selection of recipes with the option of using only one pot, this title includes recipes from succulent soups to comforting casseroles, from Steak & Kidney Stew to Thai Green Fragrant Mussels.
Include Color Illustration and Index
Keywords: One-dish meals -- Casserole cooking -- Electric cooking, Slow